A MODEL OF PROGRAMMING APPROACH FOR DETERMINING THE BIG FIVE PERSONALITY TRAITS THROUGH COLOR PREFERENCES: A MODEL OF PROGRAMMING APPROACH FOR DETERMINING THE BIG FIVE PERSONALITY TRAITS THROUGH COLOR PREFERENCES - Atanasov, Valentin; Trifonov, Tihomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Determining human behavior in a number of cases is an important, even primary, step that sets specific frameworks and guidelines for planning, constructing, and operating a wide range of structures whose focus is the human being. Based on the widely accepted theory of the Big Five Personality Traits (BFPT) and examining the existing methods used in the procedures of this theory, a set of key indicators could be derived. In the search for a scientifically proven connection between an individual’s color preferences and the predefined indicators from the BFPT, a problem arises regarding the use of methods and approaches in these procedures. In most cases, the approaches rely on the use of printed materials, which, first, limit the color spectrum, second, require a significant amount of time for preparing laboratory setups, third, lack a high degree of precision, and fourth, have limited use of mathematical tools when defining color tasks for a given individual.